Help or hindrance? The influence of Dutch on the acquisition of English phrasal verbs (Linguistics in Amsterdam, 2020)
Research has shown that English as a second language (ESL) learners find phrasal verbs (PVs) hard to acquire and often avoid these constructions. An often-neglected aspect in avoidance literature is the uncertainty of knowing the correct verb + particle pairing. The present paper investigated this by looking at Dutch ESL learners’ knowledge of verb + particle pairings as well as the influence of the L1 on L2 lexical development. To this end, over 50 Dutch learners of English at two proficiency levels were tested and compared to native speakers on English PVs that either (mis)match in form and meaning as compared to the Dutch counterpart. Results indicate that learners make more mistakes when the L1 and L2 differ in form and meaning. L1 interference is observed as learners overextend Dutch versions into English. This interference need not fossilise as advanced learners perform more like native speakers. Directions for future inquiries are provided as well.